Zinc coated urea enhanced the growth and quality of rice cultivated under aerobic and anaerobic culture. (9th May 2022) - Irshad, Muhammad; Wahid, Muhammad Ashfaq; Farrukh Saleem, Muhammad; Khan, Shahbaz; Irshad, Sohail; Matloob, Amar; Sarwar, Muhammad; Ali, Madad; Hasnain, Zuhair; Akhtar Cheema, Mumtaz
Abstract: Agricultural systems all over the world are facing extraordinary pressure in term of squeezed natural resources to meet the increasing food demand of fast growing population in recent times. Water being the most useful natural resource has become scare due to climate change and global warming as it is key input of agronomic crops particularly rice. An experiment was carried out to evaluate the impact of nitrogenous fertilizers on rice productivity under aerobic and anaerobic cultures in green house conditions. In aerobic culture, soil was kept aerated by maintaining 80–100% field capacity while flooded conditions were maintained throughout the cultivation period by putting polythene bags in pots regarding anaerobic culture. Nitrogenous fertilizers include urea, neem coated urea and zinc coated urea. All the nitrogenous fertilizers enhanced the growth, yield and quality attributes of rice plant as compared to control treatment but maximum improvement was recorded by application of zinc coated urea. Application of zinc coated urea produced maximum productive tillers, kernel length, 100- kernel weight and kernels per spikelet. Maximum transpiration rate was also observed by application of zinc coated urea. Application of zinc coated urea produced maximum normal kernels while percentage of opaque, abortive and chalky kernels was significantly reduced. Zinc coated urea was found responsible for maximum production of straw and kernel yield. Anaerobic conditions were also recorded more responsive comparatively. Among the nitrogenous fertilizers, zinc coated urea is recommended to enhance the productivity of rice with good quality kernels under anaerobic culture.